High and low contraceptive use amongst young male offenders: a qualitative interview study. Issue 4 (15th April 2014) - Buston, Katie; Parkes, Alison; Wight, Danny
Abstract : Objectives: There are high rates of fatherhood and sexually transmitted infections (STIs) among young incarcerated men. Here we focus on a sample of men incarcerated in a Scottish Young Offender Institution, analysing their accounts of their contraceptive use. Those who report low or no use of contraception are compared with those who report high use. Methods: Semi-structured interviews with 40 young male offenders, aged 16–21 years. Participants were purposively sampled using answers from a questionnaire administered to 67 inmates. Data from those men ( n =31) reporting either high ( n =14) or low/no use ( n =17) of contraception are analysed here. Results: Low users emphasise their desire for pleasure and appear fatalistic about both pregnancy and disease prevention. High users report a strong desire to protect themselves and their 'manliness' by using condoms to avoid the risk of STIs and, to a lesser extent, pregnancy. Both sets of men present themselves in a traditionally masculine way, with high users emphasising power, authority and self-control to justify their non-risk-taking contraceptive behaviour. Conclusions: The masculine narrative regarding self-protection, utilised by the high users, may be an effective method of intervention with potential and actual low users. Conventional masculinity valorises risk-taking but if particular forms of risk avoidance – condom use – can be legitimised as confirming one's masculinity it may be possible to persuade low users to adopt them. The opportunity to work with young men whilst incarcerated should be grasped.